Assessment of arterial elasticity among HIV‐positive participants with high CD4 cell counts: a substudy of the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial. (April 2015) - Baker, JV; Engen, NW; Huppler Hullsiek, K; Stephan, C; Jain, MK; Munderi, P; Pett, S; Duprez, D; ,
Abstract : Objectives: Both HIV infection and antiretroviral therapy (ART) may increase cardiovascular disease (CVD) risk. Assessments of vascular function and structure can be used to study the pathogenesis and progression of CVD, including the effects of ART and other interventions. The objective of this report is to understand methods to assess vascular (dys)function and report our experience in the Arterial Elasticity Substudy in the Strategic Timing of AntiRetroviral Treatment (START) trial. Methods: We review literature and analyze baseline data from the Arterial Elasticity Substudy, which estimated vascular (dys)function through analysis of the diastolic blood pressure (BP) waveform. Linear regression was used to study cross‐sectional associations between baseline clinical factors and small or large arterial elasticity. Results: Arterial elasticity measurement was chosen for its improved measurement reproducibility over other methodologies and the potential of small arterial elasticity to predict clinical risk. Analysis of baseline data demonstrates that small artery elasticity is impaired (lower) with older age and differs by race and between geographical regions. No HIV‐specific factors studied remained significantly associated with arterial elasticity in multivariate models. Conclusions: Longitudinal analyses in this substudy will provide essential randomized data with which to study the effects of early ART initiation on the progression of vascular disease among a diverse global population. When combined with future biomarker analyses and clinical outcomes in START, these findings will expand our understanding of the pathogenesis of HIV‐related CVD.